Destination Sustainability and Memorable Tourism Experiences - Miguel Ángel Moliner-Tena (MDPI AG, 2021)
The objective of this paper is to study the relationship between memorable tourism experiences and destination sustainability. Three hypotheses that relate dimensions of sustainability (economic, socio-cultural, and environmental) to memorable tourism experience are considered, based on a review of the literature. A questionnaire designed for that purpose was administered to 1034 tourists who stayed at five rural and sun and beach destinations in Spain. A multigroup analysis with a structural equation model was conducted to establish the differences between both destination types. The results show that destination environmental sustainability influences the memorable tourism experience, though significant differences between rural and sun and beach destinations have been detected. Age plays a moderating role: the younger the tourist the greater the influence of sustainability on memorable tourism experiences.